1992
DOI: 10.1088/0953-8984/4/18/012
|View full text |Cite
|
Sign up to set email alerts
|

Electronic distributions of states in crystalline and quasicrystalline Al-Cu-Fe and Al-Cu-Fe-Cr alloys

Abstract: Valence and conduction state distributions in a series of Al-Cu-Fe and Al-Cu-Fe-Cr alloys of different structural states and nominal compositions have been investigated by means of soft X-ray emission and photoabsorption spectroscopies. A complete description of the valence band is obtained. The DOS at EF is observed to be very low which is consistent with the high resistivity values found for the icosahedral quasicrystalline phase. The existence of a wide pseudo-gap at EF is evidenced, which is higher in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 23 publications
6
23
0
Order By: Relevance
“…On the basis of the observation of the local rearrangement of atoms upon the formation of an icosahedral structure in Al-Fe-Cu ternary alloys and by using a combination of EXAFS and XANES spectroscopy, we have proposed a model for the mechanism of structural crystal-quasicrystal transition. In summary, it should be noted that the mechanism considered here is in agreement with the conclusions about the important role of copper in the formation of electronic states on the Fermi surface in quasicrystalline Al-Cu-Fe [16]. On the basis of the X-ray photoemission study, it was shown in [16] that the Cu 3d states shift the densities of the Al 3p and Fe 3d states to higher and lower binding energies, respectively, thus facilitating the Fe3d-Al3p hybridization and total decrease in the density of states with the formation of a pseudogap on the Fermi surface.…”
Section: Discussionsupporting
confidence: 89%
“…On the basis of the observation of the local rearrangement of atoms upon the formation of an icosahedral structure in Al-Fe-Cu ternary alloys and by using a combination of EXAFS and XANES spectroscopy, we have proposed a model for the mechanism of structural crystal-quasicrystal transition. In summary, it should be noted that the mechanism considered here is in agreement with the conclusions about the important role of copper in the formation of electronic states on the Fermi surface in quasicrystalline Al-Cu-Fe [16]. On the basis of the X-ray photoemission study, it was shown in [16] that the Cu 3d states shift the densities of the Al 3p and Fe 3d states to higher and lower binding energies, respectively, thus facilitating the Fe3d-Al3p hybridization and total decrease in the density of states with the formation of a pseudogap on the Fermi surface.…”
Section: Discussionsupporting
confidence: 89%
“…In the case of QC's bearing transition-metal atoms, such as AlCu͑Fe,Ru͒ or AlPd͑Mn,Re͒, in addition to this broad minimum in the DOS, a narrow dip ͑ϳ0.1 eV width͒ due to hybridization effects involving the transition-metal bands should be also taken into account. [75][76][77][78][79] The physical existence of the electronic pseudogap has been confirmed by measurements of the specific-heat capacity, 80 photoemission, 81 soft-x-ray spectroscopies, 82 magnetic susceptibility, and nuclear magneticresonance probes. 83 Nevertheless, the relative insensitivity of the specific-heat electronic term to thermal annealing suggests that the presence of the pseudogap alone does not suffice to explain all the transport anomalies, particularly those manifesting themselves at relatively high temperatures, hence implying the influence of band-structure effects.…”
Section: Electronic Structure Modelmentioning
confidence: 99%
“…The second one concerns the existence of spiky features in the density of states ͑DOS͒ near the Fermi level. The presence of a pseudogap was theoretically predicted in order to explain the stability of quasicrystalline alloys 8 and its physical existence has received strong experimental support in the last few years, as indicated by measurements of the specific-heat capacity at low temperatures, 9 photoemission 10 and soft x-ray spectroscopies, 11 or magnetic susceptibility and nuclear magnetic resonance probes. 12 On the other hand, the existence of a spiky fine structure of the electronic DOS over an energy scale of about 10 meV has been obtained in self-consistent ab initio calculations dealing with several suitable quasicrystalline approximants.…”
Section: Introductionmentioning
confidence: 99%